2022
DOI: 10.3390/d14030197
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability in a Symbiont-Diverse Marine Host and the Use of Observational Data to Assess Ecological Interactions

Abstract: Despite a rich taxonomic literature on the symbionts of ascidians, the nature of these symbioses remains poorly understood. In the Egyptian Red Sea, the solitary ascidian Phallusia nigra hosted a symbiotic amphipod and four copepod species, with densities as high as 68 mixed symbionts per host. Correlation analyses suggested no competition or antagonism between symbionts. Ascidian mass, ash-free dry mass per wet mass (AFDM/WM), and both symbiont density and diversity per host, differed significantly among thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…Indeed, spatial and temporal variations in host abundance may lead to variations in the density of Leucothoe spp. in their hosts [23] and may explain the results of Cantor et al [36], who found a positive correlation between P. nigra biomass and the number of amphipods hosted. In addition, the results of Cantor et al [36] were based on a single sampling, which increased the random component in the study of the population of L. angraensis (see [12]) and its relationship with P. nigra.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Indeed, spatial and temporal variations in host abundance may lead to variations in the density of Leucothoe spp. in their hosts [23] and may explain the results of Cantor et al [36], who found a positive correlation between P. nigra biomass and the number of amphipods hosted. In addition, the results of Cantor et al [36] were based on a single sampling, which increased the random component in the study of the population of L. angraensis (see [12]) and its relationship with P. nigra.…”
Section: Discussionmentioning
confidence: 72%
“…Given the high morphological similarity, the occurrence in the same host, and the relatively short distance between the bays, it was assumed that the first two cases were also specimens of the new species and the P. nigra/L. angraensis association is currently considered the correct symbiotic match [23]. In some cases, L. richiardii may also have been misidentified in the past in the Mediterranean region, where it is reported to be a generalist commensal of several hosts, especially ascidians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, the ascidian can become infected by parasitic copepods that feed on its cellulose tunic (Hirose, 2000 ), suppressing the sexual reproduction of the ascidian host (Hirose et al, 2005 ). Multiple species and individuals of crustaceans can be present in an ascidian host simultaneously (Cruz‐Rivera et al, 2022 ; Kim et al, 2016 ), and residence in hosts is reportedly seasonal (Thiel, 2000 ) and dependent on the host's physiological state (White & Reimer, 2012 ).…”
Section: Introductionmentioning
confidence: 99%